Music in de German Renaissance: sources, styles and contexts - Kmetz, John (Cambridge Cambridge University Press, 1994)
This collection of fourteen essays explores the musical culture of the German-speaking realm between c. 1450 and 1600. The essays demonstrate the important role played by German speakers in the development of instrumental music in the Renaissance, in setting patterns of musical patronage, and in developing commercial music printing. The volume provides an overview of German polyphonic music in the age of Gutenberg, DÜrer and Luther, and documents the changing social status of music in Germany during a crucial epoch of its history.
This 1994 collection of fourteen essays, written by an eminent group of scholars, explores the musical culture of the German-speaking realm between c.1450 and 1600. The essays demonstrate the important role played by German speakers in the development of instrumental music in the Renaissance, the shaping of the curricula of musical education in the modern age, in setting patterns of musical patronage, in establishing congregational singing in churches, and in developing commercial music printing. The essays shed light on the music that flourished at Imperial and ducal courts, universities, parish churches, collegiate schools, as well as the homes of prosperous merchants. The volume thus provides an overview of German polyphonic music in the age of Gutenberg, Dürer and Luther and documents the changing social status of music in Germany during a crucial epoch of its history.
Keywords: 15th Century (1401-1500); 16th Century (1501-1600); Music history; Germany